Pengaruh Profitabilitas dan Harga Komoditas Minyak terhadap Harga Saham Perusahaan Migas yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2020–2024 - Ika Lista Fadila; Irvan Yoga Pardistya; Liya Megawati (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Net Profit Margin (NPM), and world oil prices on the stock prices of oil and gas supporting companies listed on the Indonesia Stock Exchange during the 2020–2024 period, motivated by the fluctuation of stock prices in the oil and gas sector influenced by both internal and external factors. The research employs a quantitative associative approach using secondary data obtained from annual financial statements, annual closing stock prices, and world oil price data. The sample was selected through purposive sampling, resulting in 55 observations, and the data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression including t-tests, F-tests, and the coefficient of determination. The results indicate that partially, ROA has a significant effect on stock prices, while NPM and world oil prices do not have a significant effect; however, simultaneously, all variables significantly influence stock prices. The Adjusted R Square value of 0.165 shows that 16.5% of the variation in stock prices can be explained by the model, while the remaining 83.5% is influenced by other factors outside the study.